2019
DOI: 10.17135/jdhs.2019.19.3.154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential of Commercial Vitamin Drinks to Induce Tooth Erosion

Abstract: Background: The market for vitamin drinks is expanding both in Korea and worldwide. However, it was difficult to find studies regarding the possibility of tooth erosion induction due to vitamin drinks. The purpose of the present in vitro study was to evaluate the effect of tooth erosion caused by a few commercial vitamin beverages on bovine teeth enamel in terms of erosion depth and fluorescence loss. Methods: Three experimental groups (vitamin drinks), a positive control group (Coca-Cola), and a negative cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The findings are consistent with previous studies that found high acidity of carbonated soft drinks and fruit juices and reported that prolonged exposure to these drinks leads to the dissolution and loss of dental hard tissues. 20,35,38 Additionally, a few studies have reported that most commercially available vitamin water products are acidic, 17,26,27 similar to our results, which identified the tested vitamin waters and herbal beverages as acidic.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings are consistent with previous studies that found high acidity of carbonated soft drinks and fruit juices and reported that prolonged exposure to these drinks leads to the dissolution and loss of dental hard tissues. 20,35,38 Additionally, a few studies have reported that most commercially available vitamin water products are acidic, 17,26,27 similar to our results, which identified the tested vitamin waters and herbal beverages as acidic.…”
Section: Discussionsupporting
confidence: 89%
“…While vitamin waters and herbal drinks have been marketed as functional drinks for health and have increasingly gained popularity, the impact of these products on dental erosion has rarely been investigated. [15][16][17]41 This study showed the erosive potential of vitamin waters and herbal beverages, indicating that long-term exposure to these drinks can cause dissolution and loss of tooth minerals. This study found that most of the tested drinks were acidic; moreover, it illustrated the erosive potential of vitamin waters, herbal drinks, carbonated soft drinks, and fruit juices.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the intake frequency of vitamin beverages has been reported to be relatively high (2∼3 times per week [19.9%] for 2∼3 weeks per month [25.5%]) 4) . Although the vitamin beverage market and consumer demand continue to increase, there is a lack of consumer awareness and consideration about the effects of these beverages on health 5) . A survey reported that a high proportion (approximately 32.9%) of the food ingredient labels of vitamin beverages are not being read by consumers 4) .…”
Section: Introductionmentioning
confidence: 99%